Effect of Eccentric Calcification of an Aortic Valve on the Implant Depth of a Venus-A Prosthesis During Transcatheter Aortic Valve Replacement: A Retrospective Study - Li, Lanlan; Liu, Yang; Jin, Ping; Tang, Jiayou; Lu, Linhe; Zhu, Guangyu; Xu, Chennian; Ma, Yanyan; Yang, Jian (Frontiers in Physiology, 2021)
Object: Our goal was to assess the implant depth of a Venus-A prosthesis during transcatheter aortic valve replacement (TAVR) when the areas of eccentric calcification were distributed in different sections of the aortic valve. Methods: A total of 53 patients with eccentric calcification of the aortic valve who underwent TAVR with a Venus-A prosthesis from January 2018 to November 2019 were retrospectively analyzed. The patients were divided into 3 groups (A, B, C) according to the location of the eccentric calcification, which was determined by preprocedural computerized tomography angiography images. The prosthesis release process and position were evaluated by contrast aortography during TAVR, and the differences in valve implant depths were compared among the 3 groups. The effects of different aortic root structures and procedural strategies on prosthesis implant depth were analyzed. Results: Eleven patients had eccentric calcification in region A; 19 patients, in region B; and 23 patients, in region C. The patients with eccentric calcification in region B had a higher risk of prosthesis migration (10.5% upward and 21.1% downward), and the position of the prosthesis after TAVR in group B was the deepest among the 3 groups. When eccentric calcification was located in region A or C, the prosthesis was released at the standard position with more stability, and the location of the prosthesis was less deep after TAVR (region A: 4.12 ±3.4 mm; region B: 10.2±5.3 mm; region C: 8.4 ±4.0 mm; region A vs. region B, P=0.0004; region C vs. region B; P=0.0360). In addition, the left ventricular outflow tract (P=0.0213) and aortic root angulation (P=0.0263) also had a significant effect on implant depth in the aortic root structure of the patients. The prosthesis size was 28.3 ±2.4 in the deep implant group and 26.4±2.0 in the appropriate implant group (P=0.0068). Conclusion: The implant depth of the Venus-A prosthesis is closely related to the distribution of eccentric calcification in the aortic valve during TAVR. Surgeons should adjust the surgical strategy according to aortic root morphology to prevent prosthesis migration.